2014
DOI: 10.3390/s140713102
|View full text |Cite
|
Sign up to set email alerts
|

A New Electrochemical Sensor Based on Task-Specific Ionic Liquids-Modified Palm Shell Activated Carbon for the Determination of Mercury in Water Samples

Abstract: In this study, a potentiometric sensor composed of palm shell activated carbon modified with trioctylmethylammonium thiosalicylate (TOMATS) was used for the potentiometric determination of mercury ions in water samples. The proposed potentiometric sensor has good operating characteristics towards Hg (II), including a relatively high selectivity; a Nernstian response to Hg (II) ions in a concentration range of 1.0 × 10−9 to 1.0 × 10−2 M, with a detection limit of 1 × 10−10 M and a slope of 44.08 ± 1.0 mV/decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…This reagent is also an IL, such as Aliquat 336, having both the same cationic part but bearing a thiosalicylate anion instead of the chloride. TOMATS has proven its efficiency in terms of mercury extraction when used to impregnate palm shell carbon (Ismaiel et al 2013) or when incorporated in an electrochemical sensor for the determination of this metal (Ismaiel et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This reagent is also an IL, such as Aliquat 336, having both the same cationic part but bearing a thiosalicylate anion instead of the chloride. TOMATS has proven its efficiency in terms of mercury extraction when used to impregnate palm shell carbon (Ismaiel et al 2013) or when incorporated in an electrochemical sensor for the determination of this metal (Ismaiel et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that probability value (′p′ value) was greater than alpha (> 0.05) which provided the evidence that the proposed electrode can be suitably used to check the presence of Hg 2+ in the real samples. Comparability of proposed electrode with reported sensors selective for mercury ions: The working of proposed electrode was compared with the reported sensors selective for mercury [40][41][42][43][44] and found that electrode based on chromium(III) boratotungstophosphate was superior with respect to its properties (Table-11).…”
Section: Analytical Applicationsmentioning
confidence: 97%
“…Nucleic acid analysis using biosensing strategies has been an attracting topic in many fields including gene analysis, clinical disease diagnosis, biological, environmental, pharmaceutical and forensic applications [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Several detection techniques such as optic [ 9 , 10 ], acoustic [ 11 ], quartz crystal microbalance [ 12 ], and different electrochemical techniques [ 1 , 2 , 4 , 5 , 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] have been used for nucleic acid analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Effective immobilization of oligonucleotides onto the surface of analysis platform has been one of the key features for the successful design of biosensor platforms [ 1 , 2 , 4 , 5 , 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Ionic liquids (ILs) are known as low-melting organic salts and mostly liquid at room temperature.…”
Section: Introductionmentioning
confidence: 99%